Development of a web-based registration system for prospective parking attendants for data management efficiency - Atman Lucky Fernandes; Ghea Paulina Suri; Yasmin Hamidah Nur Ghaliah; Yera Wahda Wahdi (Researcher and Lecturer Society, 2025)
This study aims to develop a web-based registration system for prospective parking attendants at the UPTD Parking Service in the Transportation Department of Batam City. Currently, the process of managing prospective parking attendant data is done manually, leading to time-consuming registration procedures. The absence of a proper information system makes it difficult for prospective parking attendants to find information about the registration process at the Batam City Transportation Department. This system was developed by using PHP programming and MySQL database. The development follows the SDLC Waterfall model, which consists of five phases: requirements analysis, system design, coding, program testing, and system implementation. The system was modelled by using Unified Modeling Language (UML), including use case diagrams, activity diagrams, class diagrams, and sequence diagrams. System testing was conducted by using black-box testing and tested by users. The results of this study include the requirements analysis, system design with UML modeling, and eight supporting tables for the development of the web-based application. The system has been tested on local host and through black-box testing, and it is deemed successful in assisting the management of prospective parking attendant registration. However, the application is limited to the admin and user pages. There is a need for data classification on the system dashboard to present a more executive-level display in line with the registration form for prospective parking attendants. Additionally, there is a need for improvements in human resources to ensure proper operation and maintenance of the system.